Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.5194/gmd-9-111-2016
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of cloud condensation nuclei activity for organic compounds using functional group contribution methods

Abstract: Abstract.A wealth of recent laboratory and field experiments demonstrate that organic aerosol composition evolves with time in the atmosphere, leading to changes in the influence of the organic fraction to cloud condensation nuclei (CCN) spectra. There is a need for tools that can realistically represent the evolution of CCN activity to better predict indirect effects of organic aerosol on clouds and climate. This work describes a model to predict the CCN activity of organic compounds from functional group com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 96 publications
3
42
0
Order By: Relevance
“…additionally investigated binary salt + nonionic surfactant mixtures and observed that the CCN activation efficiency was, in some cases, actually suppressed relative to ideal mixing. Similarly, Prisle et al (2010) observed that the CCN activation efficiency of binary NaCl + ionic surfactant mixtures was reasonably well described assuming the surfactants to be fully soluble with no impact on surface tension. In this work we will clarify why such highly surface-active species can have, and in the case of fatty acids do have, little impact CCN activation efficiency.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…additionally investigated binary salt + nonionic surfactant mixtures and observed that the CCN activation efficiency was, in some cases, actually suppressed relative to ideal mixing. Similarly, Prisle et al (2010) observed that the CCN activation efficiency of binary NaCl + ionic surfactant mixtures was reasonably well described assuming the surfactants to be fully soluble with no impact on surface tension. In this work we will clarify why such highly surface-active species can have, and in the case of fatty acids do have, little impact CCN activation efficiency.…”
Section: Introductionmentioning
confidence: 78%
“…There have also been direct single particle surface tension measurements for aerosols at sub-saturated humidities . However, it has been suggested that the effects of surface tension lowering on cloud droplet activation are offset by depletion of solutes from the bulk solution as they partition to the surface of microscopic droplets having high surface-area-to-volume ratios (Prisle et al, 2010;Asa-Awuku et al, 2009;Sorjamaa et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Optical microscopy images of supermicron samples of MT-and IP-derived SOA show that the RH-dependent phase behavior of these two SOA types is different (Figure 1 and Table S1). For the MT-SOA a single organic-rich phase was observed at <95% RH, but at~95% RH, liquid-liquid phase separation occurred to form two phases: an organic-rich and a water-rich phase (Figure 1b) [Song et al, 2012;Krieger et al, 2012;You et al, 2014;Renbaum-Wolff et al, 2016;Petters et al, 2016]. For IP-SOA, one single phase was observed over the entire RH range (Figure 1a).…”
Section: Resultsmentioning
confidence: 98%
“…For instance, chemical characteristics of water-soluble organic matter (WSOM) have been intensively investigated, revealing that WSOM predominantly consists of levoglucosan-like species, carboxylic acids, aldehydes, ketones, aliphatic alcohols, and polyacids (Decesari et al, 2000;Peng et al, 2001;Suzuki et al, 2001;MayolBracero et al, 2002;Chan et al, 2005;Psichoudaki and Pandis, 2013). Recently, the important roles of functional groups in water uptake properties were also investigated by both theoretical and experimental approaches (Suda et al, 2014;Petters et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The complexity in chemical composition inhibits understanding their water uptake properties at molecular levels (Asa-Awuku et al, 2008;Psichoudaki and Pandis, 2013;Riipinen et al, 2015). To overcome this difficulty, classification of organic compounds using multiple solvents Polidori et al, 2008;Chen et al, 2016), liquid-liquid extraction using 1-octanol and water (Kuwata and Lee, 2017), and solid-phase extraction (Asa-Awuku et al, 2008) has been conducted. Functional-group analysis of segregated organic matter has also been demonstrated as a strong tool to characterize complex mixture of organic compounds (Chen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%